FRI0144 Patient-reported outcomes with sarilumab in patients with rheumatoid arthritis are similar regardless of primary or secondary failure with tumour necrosis factor inhibitors. (12th June 2018) - Strand, V.; Boklage, S.; Mangan, E.; Reaney, M.; Iglesias-Rodriguez, M.; Kimura, T.
Abstract : Background: Sarilumab is a human monoclonal antibody that binds membrane and soluble IL-6 and was recently approved for the treatment of moderate-to-severe rheumatoid arthritis. Among inadequate responders to a TNF inhibitor (TNFi), patients may respond differently to sarilumab depending on whether they had a primary (1°) failure or initially responded but then subsequently lost response (secondary [2°] failure). Objectives: To understand if changes in patient reported outcomes (PROs) differ among patients with 1° or 2° TNFi failure. Methods: In TARGET (NCT10709758 ), patients with intolerance or an inadequate response to TNFi were randomised to placebo or sarilumab 150 mg or 200 mg plus csDMARD. For patients with an inadequate response to TNFi (92% of the sample), 1° or 2° failure was investigator-determined at enrollment. The following PROs were assessed at Week 0 (treatment initiation) and Week 24: HAQ-DI, patient global assessment of disease visual analogue scale (VAS), pain VAS, SF-36, morning stiffness VAS, EQ-5D, and Rheumatoid Arthritis Impact of Disease (RAID) scale. All scales produce global (total) scores, except the SF-36 which has eight domains and two summary scores (physical and mental component scores [PCS and MCS]) and the EQ-5D which has a single index utility score and a global health VAS. The PRO change from baseline was analysed through mixed model repeated measures with treatment, region, number of prior TNFis, baseline of the PRO analysed, visit, treatment-by-visit interaction, 1° and 2°subgroup, treatment-by-subgroup interaction, and treatment-by-visit-by-subgroup interaction. Post-hoc analysis of the sarilumab 200 mg data are reported here as this is the recommended dose of sarilumab. Results: In this post-hoc analysis, 174 of 181 patients in the placebo group and 167 of 184 in the sarilumab 200 mg group were classified as TNFi 1° or 2° failures (the remaining patients were classed as intolerant or other and not included in this analysis); 75 and 64 were 1° and 99 and 103 were 2° treatment failures in the placebo and the sarilumab 200 mg groups, respectively. At Week 24, changes in all PROs were numerically similar in the 1° or 2° TNFi failures for both the sarilumab 200 mg and placebo groups (table 1). Furthermore, treatment-by-subgroup interaction testing did not show a statistically significant interaction of TNFi failure status and PRO outcome (all interaction P -values>0.05). Treatment emergent adverse events occurred in 65.6% of sarilumab 200 mg patients in the 1° failure group and 63.1% in the 2° failure group and were consistent with safety data reported previously. Conclusions: In TNFi inadequate response patients, following treatment with sarilumab 200 mg +csDMARD, changes in PRO outcomes were similar, regardless of whether they had experienced 1° or 2° TNFi failure, suggesting that sarilumab is suitable for both 1° and 2° TNFi failure patients. Acknowledgements: The study was funded by Sanofi and Regeneron Pharmaceuticals, Inc. Disclosure of Interest: V. Strand Consultant for: AbbVie, Amgen, AstraZeneca, Biogen, BMS, Celltrion, CORRONA, Crescendo, Genentech/Roche, GSK, Janssen, Eli Lilly, Novartis, Pfizer, Regeneron Pharmaceuticals Inc., Sandoz, Sanofi and UCB, S. Boklage Shareholder of: Regeneron Pharmaceuticals, Inc., Employee of: Regeneron Pharmaceuticals, Inc., E. Mangan Shareholder of: Regeneron Pharmaceuticals, Inc., Employee of: Regeneron Pharmaceuticals, Inc., M. Reaney Shareholder of: Sanofi, Employee of: Sanofi, M. Iglesias-Rodriguez Shareholder of: Sanofi, Employee of: Sanofi, T. Kimura Shareholder of: Regeneron Pharmaceuticals, Inc., Employee of: Regeneron Pharmaceuticals, Inc.